2019 IEEE Symposium Series on Computational Intelligence (SSCI) 2019
DOI: 10.1109/ssci44817.2019.9003114
|View full text |Cite
|
Sign up to set email alerts
|

Tutorial and Survey on Probabilistic Graphical Model and Variational Inference in Deep Reinforcement Learning

Abstract: Probabilistic Graphical Models and Variational Inference play an important role in recent advances in Deep Reinforcement Learning. As a self-inclusive tutorial survey, this article illustrates basic concepts of reinforcement learning with Probabilistic Graphical Models and offers derivation of some basic formula as a recap. Reviews and comparisons on recent advances in deep reinforcement learning are made from various aspects. We offer Probabilistic Graphical Models, detailed explanation and derivation to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Statistical modelling has been extremely successful in the context of modern machine learning and moment matching is an efficient technique to do so. We refer the reader to the surveys and references therein [21,38,51,62].…”
Section: Random Feature Injectionmentioning
confidence: 99%
“…Statistical modelling has been extremely successful in the context of modern machine learning and moment matching is an efficient technique to do so. We refer the reader to the surveys and references therein [21,38,51,62].…”
Section: Random Feature Injectionmentioning
confidence: 99%
“…DEC-POMDP can be solved using control as inference [ 16 , 17 ]. Control as inference is a framework to interpret a control problem as an inference problem by introducing auxiliary variables [ 18 , 19 , 20 , 21 , 22 ]. Although control as inference has several variants, Toussaint and Storkey showed that the planning of MDP can be interpreted as the maximum likelihood estimation for a latent variable model [ 18 ].…”
Section: Introductionmentioning
confidence: 99%